A New Orthodontic-Surgical Approach to Mandibular Retrognathia - Vale, Francisco (2021)
(1) Background: Mandibular deficiency is one of the most common growth disorders of the facial skeleton. Recently, distraction osteogenesis has been suggested as the treatment of choice for overcoming the limitations of conventional orthognathic surgery; (2) Methods: A new custom-manufactured dental-anchored distractor was built and anchored in the first molar and lower canine. It consists of a stainless-steel disjunction screw, adapted and welded to the orthodontic bands through two 1.2 mm diameter connector bars with a universal silver-based and cadmium-free solder; (3) Results: The distractor described can be a useful tool to correct mandibular retrognathia and is better tolerated by patients, especially in severe cases; (4) Conclusions: The dental-anchored distractor increases the anterior mandibular bone segment without affecting the gonial angle or transverse angulation of the segments and avoids posterior mandibular rotation, overcoming the limitations of conventional surgical treatment.